Lithium Ion Mobility in Lithium Phosphidosilicates: Crystal Structure, 7Li, 29Si, and 31P MAS NMR Spectroscopy, and Impedance Spectroscopy of Li8SiP4 and Li2SiP2. Issue 49 (27th October 2016) - Toffoletti, Lorenzo; Kirchhain, Holger; Landesfeind, Johannes; Klein, Wilhelm; van Wüllen, Leo; Gasteiger, Hubert A.; Fässler, Thomas F.
Abstract: The need to improve electrodes and Li‐ion conducting materials for rechargeable all‐solid‐state batteries has drawn enhanced attention to the investigation of lithium‐rich compounds. The study of the ternary system Li‐Si‐P revealed a series of new compounds, two of which, Li8 SiP4 and Li2 SiP2, are presented. Both phases represent members of a new family of Li ion conductors that display Li ion conductivity in the range from 1.15(7)×10 −6 Scm −1 at 0 °C to 1.2(2)×10 −4 Scm −1 at 75 °C (Li8 SiP4 ) and from 6.1(7)×10 −8 Scm −1 at 0 °C to 6(1)×10 −6 Scm −1 at 75 °C (Li2 SiP2 ), as determined by impedance measurements. Temperature‐dependent solid‐state 7 Li NMR spectroscopy revealed low activation energies of about 36 kJ mol −1 for Li8 SiP4 and about 47 kJ mol −1 for Li2 SiP2 . Both compounds were structurally characterized by X‐ray diffraction analysis (single crystal and powder methods) and by 7 Li, 29 Si, and 31 P MAS NMR spectroscopy. Both phases consist of tetrahedral SiP4 anions and Li counterions. Li8 SiP4 contains isolated SiP4 units surrounded by Li atoms, while Li2 SiP2 comprises a three‐dimensional network based on corner‐sharing SiP4 tetrahedra, with the Li ions located in cavities and channels. Abstract : Tetrahedra and Li ions at their best : The new Li‐Si‐P ternary phase compounds Li8 SiP4 and Li2 SiP2 are the starting point of a large compound class. Both compounds form structures based on SiP4 tetrahedral building blocks and reveal a significant lithium ion mobility. The compounds were characterized by XRD and solid‐state NMR, and Li ion mobility was investigated by impedance and temperature‐dependent NMR spectroscopy.